CRITERIA FOR EVALUATING POLLUTION OF WATER BODIES, DRINKING WATER AND POPULATION MORBIDITY - Islam A. Usmanov; Aygul Zh. Ilyasova (Central Asian Journal of Medicine, 2025)
The article is devoted to the criteria development for assessing the surface water bodies pollution levels, drinking water and the risk of the spread of intestinal infections among the population. The developed criteria are based on the principle of priority maintaining importance the health of the population living in anthropogenic pollution conditions. The proposed criteria are based on the ranking, in points, of estimated indicators according to their health hazard degree. Four main pollution gradations are proposed: allowable-1, moderate-2, high-3 and extremely high-4. Accordingly, with the proposed gradation, the health hazard level for the pollution degree is assessed as permissible, causing concern, dangerous and extremely dangerous. It is proposed to use the methodology of the developed criteria for zoning, according to the health hazard degree, of contaminated surface water bodies and drinking water in order to reduce the incidence of intestinal infections in the population.